Evaluation of success and/or failure of endodontic treatment in non-vital teeth performed at the School of Dentistry at the Universidad del Valle. Case series - Ochoa, Luis; Moreno, Stevan; Piarpuzán, David; Rodríguez, Patricia; Herrera, Adriana; Moreno, Sandra (Revista Estomatología, 2014)
Introduction: The endodontic treatment in non-vital teeth is directed to the elimination of the infection through the biofilm removal biomechanics and remnants of necrotic tissue, in order to eliminate infection and generate periapical tissue repair.Objective: To determine the success or failure of endodontic treatment in non-vital teeth performed by dental students under supervision.Materials and methods: In this article 3 clinical cases of patients undergoing endodontic procedures with non-vital pulps track 4 and 6 years are presented.Results: Two of the 3 cases show a process of incomplete periapical tissue regeneration at the time of observation. The third case shows a process of subsequent periodontal disease to endodontics leading to tooth loss.Conclusions: Is necessary to conduct a study with a sample size calculated to determine what percentage of success and failure of endodontic treatment in non-vital teeth, performed by undergraduate dental students under supervision, and to determine those factors that directly influence both outcomes.